Using two-pyroxene mafic granulites to reconstruct ultra-high temperatures and the retrograde P–T path of metamorphism in the Socorro-Guaxupé Nappe (Southern Brasília Orogen, SE Brazil) - Silva, Otavio Sant’ Anna G. [UNESP]; Luvizotto, George L. [UNESP]; Fumes, Regiane A. [UNESP]; Moraes, Renato; Junior, George W. Clemence [UNESP]; de Oliveira, Marcos Aurelio F. [UNESP] (Springer Nature, 2024)
Abstract: In the southernmost part of the Southern Brasília Orogen (SE Brazil), regional ultra-high temperature metamorphism has been reported mainly in garnet-bearing granulites and (garnet)-orthopyroxene-bearing leucosomes at the base of the Socorro-Guaxupé Nappe, but detailed petrological studies focusing on garnet-absent mafic granulites at the upper crustal levels of this terrain are still scarce and the tectonic setting in which these extreme thermal conditions were attained are still under debate. In this study, we focus on reconstructing the metamorphic P–T paths of (garnet-absent) mafic granulites at intermediate crustal levels of the Socorro-Guaxupé Nappe using petrography, compositional maps, phase diagram modelling and Ti-in-quartz geothermometry. Our results indicate that the mafic granulites record peak P–T conditions of ~ 970 °C and 9.0–9.5 kbar (thermobaric ratio of ~ 1078 °C GPa−1) and their retrograde paths are characterized by both decompression and cooling, down to ~ 840–850 °C and 5.5–6.0 kbar. Our peak temperature results are consistent with other estimates for granulites and orthopyroxene-bearing leucosomes throughout the nappe, but the (peak) pressure results indicate points to its decrease towards the structural top. The similarity of retrograde paths throughout the Guaxupé Nappe suggests similar exhumation dynamics at different crustal depths. Furthermore, a prominent decompression vector along with the thermal peak, indicated by intergrowth microtextures and chemical zoning, coupled with compositional isopleths, suggests regional metamorphism during the continental collision between the Paranapanema and the São Francisco paleoplates. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Compositional maps; Phase diagram modelling; Socorro-Guaxupé nappe; Ti-in-quartz geothermometry; Ultra-high temperature granulites